PRE EXTENSION DEMONSTRATION OF ORANGE FLESHED SWEET POTATO VARIETIES AT MIDLAND DISTRICTS OF GUJI ZONE, SOUTHERN OROMIA, ETHIOPIA - Korji, Dembi; Kebede, Basha; Bobo, Tekle (Bangladesh Journal of Multidisciplinary Scientific Research, 2023)
This study examines an on-farm demonstration of an improved orange-fleshed sweet potato. The role of sweet potatoes in household nutrition and health benefits is highly recognized in developing countries like Ethiopia. Hence, promoting such nutrition-sensitive crops through demonstrations is significant for farmers. This demonstration was piloted to assess farmers’ feedback on orange-fleshed sweet potatoes and evaluate the performance of improved varieties of two midlands of the Guji zone. This study used NASPOT 12 and NASPOT 13 to improve orange-fleshed and local varieties. Each variety was planted on 10mx10m plots of 10 farmers’ land. Training and the mini-field day were used to promote orange-fleshed sweet potatoes. The collected data for this demonstration was analyzed through descriptive statistics and description forms. The result indicated that NASPOT 13, NASPOT 12, and the local variety gave 142 qt/ha, 114 qt/ha, and 93 qt/ha, respectively. There were more root tuber/ plants in NASPOT 13 and NASPOT 12 than in the local variety. Both improved varieties performed well in the Adola Rede and Wadera districts. The findings of this study suggest that despite the higher yield of improved varieties, farmers did not prefer NASPOT 13 and NASPOT 12 due to the sweetness of varieties that were not like the local variety. Farmers preferred the improved orange-fleshed sweet potato varieties for livestock feed. Breeding and adaptation of sweet potatoes in the study areas are needed to identify household consumption varieties. Therefore, until new varieties are identified, farmers should continue sweet potato production using the array in their hands.JEL Classification Codes: N75, O13, O32, Q16.